Authenticity determination of honeys with non-extractable proteins by means of elemental analyzer (EA) and liquid chromatography (LC) coupled to isotope ratio mass spectroscopy (IRMS). (1st February 2018) - Dong, Hao; Xiao, Kaijun; Xian, Yanping; Wu, Yuluan
Highlights: Honeys with non-extractable protein were evaluated systematically for the first time. EA-IRMS and LC-IRMS were suitable for measurement of adulteration in honeys. Honeys with non-extractable protein were all identified as adulterated with C-4 or C-3 sugars. Large numbers of samples were analyzed to ensure reliability. Result obtained is highly recommended as a supplement to AOAC 998.12 method. Abstract: The present work aims to systematically demonstrate the authenticity of honeys with non-extractable proteins for the first time, by means of EA-IRMS and LC-IRMS. Fifty-three pure honeys of various botanical and geographical origins were studied and a criterion on the basis of the stable carbon isotope ratio characterization of total honey and the main sugars was established for pure honeys. Parameters such as δ 13 C values of total honey and the main sugars were well utilized to identify honeys with non-extractable proteins. Thirty-five honeys from which protein could not be extracted were all identified as adulterated with C-4 sugars or C-3 sugars. The use of isotopic compositions and some systematic differences permit the honeys with non-extractable proteins to be reliably identified. The findings obtained in this work could supplement the AOAC 998.12 C-4 sugar method, with regard to honeys from which protein cannot be extracted.